Use of BIM 4D Models to Improve the Dynamism of Construction Layout Planning in the Structural Stage of Multifamily Housing in Metropolitan Lima - Huacre, Yhoel (2025)
Multifamily housing projects are developed in different stages of construction, each of which requires a specific site layout. This construction layout is a fundamental tool for planning the physical distribution of temporary installations at the worksite, ensuring order that does not disrupt workflows and maintains productivity. However, one of the main causes of inadequate layout planning is the poor dynamic analysis resulting from using a static layout, traditionally represented in AutoCAD drawings. For this reason, this research focuses on improving the dynamism of site layout planning in multifamily housing projects in Metropolitan Lima; specifically, in the structural stage, using 4D BIM models. The methodology used in this study is developed through the following steps: Analysis of the information gathered from the interviews and surveys conducted with experts; Determination of the traditional site layout process of the three evaluated projects; Development of the 4D BIM model; and Implementation of the model in the selected project. Finally, the implementation of the proposed 4D BIM model in the project results in a significant improvement of the dynamism in the temporary works planning, since it allows visualizing the relocations of temporary facilities during the project simulation and allows detecting temporary interferences. In addition, a more exhaustive analysis of the relocations of the temporary facilities on the job site is achieved, which facilitates better planning of the site layout.